(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2023)
As the world careers into perpetual destruction fired by a greed for power and land leading to war, violence, hunger and pollution of the planet, people are marching across the world in horror and incredulity at the unimaginable suffering of Palestinians - as well as many Israelis of course. Every decade brings its own struggles, accompanied by strikes, demonstrations, rallies, protests, sit-ins, flash mobs, whatever. Over our lifetimes I, and countless others, have lost count of the number of demonstrations we have participated in to make our voices heard. We are used to hearing speaker after speaker (often male) blowing their own trumpets and making stirring speeches with which the majority of us agree. However, organisers of protests would do well to think seriously about ways in which to include music and song in marches and rallies. Why? What is the purpose of political song? I firmly believe in the necessity of political song as an integral part of public protest; to uplift and inspire the cause and, in so doing, enrich our culture. I’d like to think that younger musicians, as artists, feel strongly enough to acknowledge and support popular struggles through their music and song. I witnessed how cultural events flourished during the Scottish Independence campaign leading up to the Referendum in 2014, when the National Collective was active and bursting at the seams with young people entertaining us. Makes you think!